Gendered Disruptions in Human Development: Women’s Education and HDI Trends in Afghanistan, 1990–2023 - Shamila Saba (Publication of the International Journal and Academic Research, 2026)
Women’s education is widely recognised as a core condition of human development, yet its developmental effects remain fragile where educational rights are politically contingent. This article examines how shifts in women’s access to education correspond with Afghanistan’s Human Development Index (HDI) trajectory from 1990 to 2023. Methodologically, it adopts a qualitative longitudinal case study combining descriptive HDI trend analysis with process tracing and documentary evidence from UN agencies, the World Bank, and international human rights organisations. The analysis shows that Afghanistan’s HDI rose from 0.284 in 1990 to 0.480 in 2014, reflecting partial development gains during periods of educational expansion and post-2001 reconstruction. However, these gains remained fragile. Following the 2021 political rupture, HDI declined to 0.473, while mean years of schooling fell from 3.0 in 2021 to 2.5 in 2022–2023. Although HDI partially recovered to 0.496 in 2023, with expected years of schooling around 10.8 and life expectancy reaching 66.0 years, this apparent stabilisation did not indicate substantive recovery in women’s capabilities. Instead, continued restrictions on secondary and higher education suggest a widening gap between aggregate development indicators and gendered access to agency, human capital formation, and public participation. The article argues that women’s education should be understood as a structural condition of sustainable human development in fragile and conflict-affected contexts.